A COMPARATIVE STUDY OF NEOLOGISM FORMATION IN CONTEMPORARY UZBEK AND ENGLISH - Ruzmuratova Aziza Anvarovna (Bright Mind Publishing, 2025)
This paper explores how contemporary Uzbek and English generate and absorb new words, highlighting the balance between traditional word-formation and borrowing. By analyzing examples from media, youth speech, and online discourse, the study shows how globalization, technological progress, and cultural policy shape lexical innovation in both languages. While both English and Uzbek display universal neological strategies, their historical contexts and attitudes toward foreign influence differ significantly.
Keywords: Neologism, word formation, borrowing, Uzbek language, English language, lexicology, globalization.